Exploring EFL Learners’ Perceptions of Phonological Awareness in Improving English Pronunciation: A Psycholinguistic Perspective - Andini, Sabilla Ayu; Nst, Mutiara Ramadhan; Harahap, Syalwa Syafitri; Barus, Putri Ananta Sari; Lubis, Yani (MUDABBIR Journal Research and Education Studies, 2025)
This study aims to explore the perceptions of English as a Foreign Language (EFL) learners regarding the role of phonological awareness in improving English pronunciation from a psycholinguistic perspective. The study uses a descriptive qualitative approach involving twelve university level EFL students in Indonesia. Data were collected through semi structured interviews and analyzed using thematic analysis.The results of the study show that most learners view phonological awareness as an important foundation for understanding and producing English sounds more accurately. Awareness of the differences between spelling and pronunciation, sound structure, and suprasegmental aspects helps learners identify previously unnoticed pronunciation errors. However, this study also found that learners still face phonological challenges, especially in distinguishing long and short vowels, pronouncing sounds that do not exist in their native language, and applying word stress and intonation consistently. In addition, increased phonological awareness encourages learners to develop more reflective and metacognitive learning strategies, such as minimal pairs exercises, imitation of native speakers, and recording their own voices. Overall, this study confirms that phonological awareness plays an important role in the development of English pronunciation in EFL learners. The findings of this study have pedagogical implications for pronunciation teaching by emphasizing the importance of explicitly integrating phonological awareness in English language learning.